(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pranata B, Kusuma AB, Sabariah V, Kim HW, Andriwiyono S. 2022. Environmental DNA metabarcoding reveals biodiversity marine fish diversity of a small island at Manokwari District, West Papua, Indonesia. Biodiversitas 23: 5982-5988. The uniqueness of small island biodiversity becomes very important to study. Molecular approaches to collecting biodiversity information are currently quite developed. Manokwari district, which is located at the head of Papua Island, Indonesia, has very diversity of marine resources, especially coral reef fish. Currently, we successfully identified marine fish in the coral reef fish ecosystem of Lemon and Mansinam Island. Environmental DNA on Lemon Island and Mansinam Island was successfully carried out. This small island area is located in Manokwari District, Papua, which has a high biodiversity potential, including fishery resources. The MiFish pipeline is used in this Metabarcoding approach by combining water samples from Lemon Island and Mansinam Island. We filtered 1 liter of marine water and pool together from fourteen sampling sites for genomic DNA extraction. A total of 101,001 reads (88.31%) were assigned to 34 species. From the environmental DNA metabarcoding analysis results, the Pomacentridae (8 species), which are reef fish, dominate in this area. Besides, Acanthuridae, Carangidae, and Lutjanidae were identified in this area, which as coral reef fish associates. The results of this environmental DNA also identified 2 species from the Family Scombridae, namely Gymnosarda unicolor and Thunnus obesus. This information is expected to support the sustainable management of the Lemon Island and Mansinam Island Areas for tourism and conservation activities.